(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
Children explain all the differences in the size of objects with the words big and small, that is, with words used to determine the mutual ratio of objects according to their overall size. Children do not use words that allow us to accurately categorize the difference between things based on a single sign. Therefore, babies have only one character (length, width or height) that is the same (equal); it is necessary to teach the use of words such as thicker, thinner, the same (equal) in thickness. When separating one or another symbol for the first time, only things that differ from each other with this symbol are compared